KEBIJAKAN FORMULASI PENGATURAN PIDANA PENJARA TERBATAS DALAM PERUNDANG-UNDANGAN INDONESIA PERSPEKTIF IUS CONSTITUENDUM - Putu Sekarwangi Saraswati (Jurnal Hukum Saraswati (JHS), 2020)
One of the efforts to tackle crime is to use criminal law with criminal sanctions. The type of criminal sanction that is most often used to tackle crime problems is imprisonment. Meanwhile, in its development, imprisonment is a type of criminal sanction that is currently receiving sharp scrutiny from experts. Many sharp criticisms have been directed at this type of criminal deprivation of independence, both in terms of its effectiveness and in terms of the other negative consequences that accompany it. In the new Penal Code Concept Book I in 1982 proposed a type of "new" criminal in the form of "criminal supervision" as an alternative to imprisonment. Prison convicts and criminal supervision actually are two philosophically contradictory concepts, because on the one hand imprisonment requires the convicted to carry out his crime within the institution, and on the other hand the criminal oversight requires the convicted to undergo his crime outside the institution (in the community), but still under supervision. Keywords: , ,